2020
DOI: 10.3389/fonc.2020.01016
|View full text |Cite
|
Sign up to set email alerts
|

Co-incidence of Human Papillomaviruses and Epstein–Barr Virus Is Associated With High to Intermediate Tumor Grade in Human Head and Neck Cancer in Syria

Abstract: High-risk human papillomaviruses (high-risk HPVs) have been recently reported to be co-present with Epstein-Barr virus (EBV) in different types of human cancers including head and neck (HN), where they can cooperate in the initiation and/or progression of this cancer. Accordingly, we herein explored the prevalence of high-risk HPVs and EBV in 80 HN cancer tissues from the Syrian population using polymerase chain reaction, immunohistochemistry, and tissue microarray methodologies. We report that high-risk HPVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…In our present study, we explored the copresence of high-risk HPVs and EBV in human CRC cases in the population of Lebanon. Interestingly, it has been recently pointed out that these oncoviruses can be copresent in several types of human cancers including cervical, oral, breast, and CRC, and their copresence varies from 12 to 50% of the cases [ 42 , 43 , 44 , 45 , 46 , 47 , 75 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Although, various studies reported an association between EBV presence and CRC [ 35 ], evidence on the role of EBV in CRC is contradictory since the majority of studies that indicate a positive association are based on PCR or IHC assays, alone or in combination with other techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study, we explored the copresence of high-risk HPVs and EBV in human CRC cases in the population of Lebanon. Interestingly, it has been recently pointed out that these oncoviruses can be copresent in several types of human cancers including cervical, oral, breast, and CRC, and their copresence varies from 12 to 50% of the cases [ 42 , 43 , 44 , 45 , 46 , 47 , 75 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Although, various studies reported an association between EBV presence and CRC [ 35 ], evidence on the role of EBV in CRC is contradictory since the majority of studies that indicate a positive association are based on PCR or IHC assays, alone or in combination with other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that the copresence of HPVs and EBV is associated with tumor grade and stage in human carcinomas [ 43 , 45 , 46 , 47 , 91 ]. Accordingly, we found in our study that HPVs and EBV are copresent in 28% of the CRC samples in Lebanon.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our previous studies exploring HPV and EBV in different types of cancers using PCR and IHC yielded comparable results. 29 , 41 , 84 , 85 …”
Section: Discussionmentioning
confidence: 99%
“…Gene amplification (polymerase chain reaction) is a PCR technology invented in April 1983 by Kary B. Mullis who received the Nobel Prize in Chemistry for this in 1993. It is a biomolecular technique that allows the exponential amplification in vitro of a given DNA sequence defined as target DNA [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%